Representing the South Pacific : colonial discourse from Cook to Gauguin - Edmond, Rod (Cambridge University Press, 1997)
This book examines how the South Pacific was represented by explorers, missionaries, travellers, writers, and artists between 1767 and 1914 by drawing on history, literature, art history, and anthropology. Edmond engages with colonial texts and postcolonial theory, criticising both for their failure to acknowledge the historical specificity of colonial discourses and cultural encounters, and for continuing to see indigenous cultures in essentially passive or reactive terms. The book offers a detailed and grounded 'reading back' of these colonial discourses into the metropolitan centres which gave rise to them, while resisting the idea that all representations of other cultures are merely self-representations. Among its themes are the persistent myth-making around the figure of Cook, the western obsession with Polynesian sexuality, tattooing, cannibalism, and leprosy, and the Pacific as a theatre for adventure and as a setting for Europe's displaced fears of its own cultural extinction.